Ferroptosis: friend or foe in cancer immunotherapy? - Robin Demuynck; Iuliia Efimova; Elena Catanzaro; Dmitri V Krysko (OncoImmunology, 2023)
Ferroptosis has gained interest due to it immunogenicity and the higher sensitivity of cancer cells to it. However, it was recently shown that ferroptosis in tumor-associated neutrophils leads to immunosuppression and negatively impacts therapy. Here, we discuss the potential implications of the two sides (friend versus foe) of ferroptosis in cancer immunotherapy.